2020
DOI: 10.1017/s1049023x20000448
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine as a Prehospital Analgesic: A Systematic Review

Abstract: Objective:Analgesia in the prehospital setting is an extremely important, yet controversial topic. Ketamine, a N-methyl D-aspartate (NMDA) receptor antagonist, has been commonly used in the prehospital setting, including recommendations by the US Department of Defense and by the Royal Australian College of Pain Medicine, despite the paucity of high-level evidence.Methods:Accordingly, a review of the literature was conducted using several electronic medical literature databases from the earliest available recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Furthermore, dose differences are not only present inter- but also intra-professionally as demonstrated by a study from a physician-staffed EMS in Germany, which showed differences in pain treatment between surgeons and anaesthesiologists, particularly regarding opioids [ 28 ]. Ketamine has been described as being safe and effective alone – even as effective as an alternative opioid – and also as being able to reduce opioid requirements when used in combination with opioids [ 26 , 29 , 30 ]. After opioids or esketamine administered alone, the by far most commonly administered combination therapy in the presented study was an opioid with esketamine, followed by a combination of an opioid with metamizole.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dose differences are not only present inter- but also intra-professionally as demonstrated by a study from a physician-staffed EMS in Germany, which showed differences in pain treatment between surgeons and anaesthesiologists, particularly regarding opioids [ 28 ]. Ketamine has been described as being safe and effective alone – even as effective as an alternative opioid – and also as being able to reduce opioid requirements when used in combination with opioids [ 26 , 29 , 30 ]. After opioids or esketamine administered alone, the by far most commonly administered combination therapy in the presented study was an opioid with esketamine, followed by a combination of an opioid with metamizole.…”
Section: Discussionmentioning
confidence: 99%
“…49 Nonetheless, the consensus is that a sub-anesthetic dose of ketamine has a role to play in the management of pain, especially when used in combination with opioids. 49,52 Additionally, ketamine use has been successful in managing pain crises following sickle cell disease, a commonly seen condition in resource-poor settings due to the poor practice of premarital genetic counseling. 53 Ketamine is a drug to consider for refractory or severe headache, despite the outcome of the THINK trial by Benish et al 54,55 In the study, intranasal ketamine was not superior to intravenous metoclopramide in managing refractory headache.…”
Section: Ketamine and Disastermentioning
confidence: 99%
“…Regarding the safety of low-dose ketamine, previous studies report a wide range in the incidence of side effects that include, most commonly, vomiting, need for intubation, dissociation or over-sedation, agitation, hallucinations, and emergence reactions [6,8,[10][11][12][13][14][15][16][17][18]. While some studies have reported zero serious adverse events, other studies have reported a moderate number of patients with one or more of the above side effects.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have reported zero serious adverse events, other studies have reported a moderate number of patients with one or more of the above side effects. Increasingly, ketamine has been used in the pre-hospital setting [1,3,4,[6][7][8][9][10][11]13,[18][19][20][21]. Indications include rapid sequence intubation by air medical crews, traumatic and nontraumatic pain management, and treatment for behavioral emergencies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation